Green and highly efficient synthesis of pyrimidine derivatives in a novel glycolic acid: urea‐based low transition temperature mixture via C–C and C–O bond formation. (26th July 2022) - Karande, Vishram; Mohire, Priyanka; Deshmukh, Shubham; Patravale, Ajinkya; Desai, Vikram; Chandam, Dattatray; Sankpal, Sandeep; Deshmukh, Madhukar
Abstract: The present works describe a highly efficient synthesis of pyrimidine derivatives through a Knoevenagel condensation followed by Michael addition and subsequent cyclization using novel designer Low Transition Temperature Mixture (LTTM) in Glycolic acid: Urea (1:1). The mixture afforded as a green solvent which plays a dual role as a reusable catalyst and solvent, simple to prepare and nontoxic. The thermal stability and working temperature range of low‐temperature mixture were identified by Thermogravimetric analysis and Differential Scanning Calorimetry. The pyrimidine derivatives synthesized via a one‐pot three‐component reaction of two moles of Barbituric/Thiobarbituric acid and one mole of aryl aldehydes reacted through Knoevenagel condensation followed by Michael addition and subsequent cyclization. The Knoevenagel intermediate formed at room temperate while at 80°C Knoevenagel intermediate further reacted with another mole of barbituric acid/Thiobarbituric acid and formed the cyclic compounds. The use of LTTM to yield vital pyrimidine molecules renders this protocol to cope with the current need for an efficient, cost‐effective, and eco‐friendly methodology. Abstract : Highly efficient synthesis of pyrimidine derivatives through a Knoevenagel condensation followed by Michael addition and subsequent cyclization using novel designer Low Transition Temperature Mixture (LTTM) in Glycolic acid: Urea (1:1).